The Mixed Layer Salinity Budget in the Northern South China Sea: A Modeling Study - Yong Chen; Canbo Xiao; Yu Zhang; Zhigang Lai (Journal of Marine Science and Engineering, 2023)
The seasonal variation in mixed layer salinity (MLS) plays a crucial role in global ocean circulation and hydrological cycle. The salinity budget of the mixed layer is important to understand the mechanism of the variation, but in the South China Sea (SCS), the details in the budget are missing due to insufficient observations. Here, we employed an eddy-resolving (horizontal grid resolution ~10 km) SCS circulation model to quantify the key physical processes in the seasonal cycling of MLS in the northern South China Sea (NSCS). Built on the success of the realistic numerical simulation for 2008–2018, the model reproduced the primary features of the observed seasonal MLS, wherein fresher waters are present in the region during the summer monsoon and salty waters appear along the slope during the winter monsoon. According to the salinity budget that was calculated during model execution, the term for air–sea freshwater flux and meridional advection represent the primary freshwater input in the summer and winter, respectively, while vertical processes including vertical mixing and entrainment form the major balancing terms in the budget. In different regions of the NSCS, vertical mixing can play a dominant role in the vertical processes, but the associated seasonality is different for regions of strong internal wave influence and regions of strong horizontal advection influence. In the winter, the intrusion and spreading of western Pacific water over the NSCS could modify the MLS structure and cause larger vertical entrainment than mixing in regions where the effect of mixing decreases with the slackening of the seasonal internal wave activities. Overall, the analysis of the ML salinity budget reveals that vertical mixing, together with vertical entrainment, is vital to maintaining the seasonal variation in MLS of the NSCS.